Loeffler’s Endocarditis- A cause of endomyocardial fibrosis in a patient of juvenile idiopathic arthritis: A Case Report - Khaliq, Taqdees; Shah, Sarah Azam; Saleem, Dr Saad Saleem; Qureshi, Safina Hameed; Iqbal, Dr Hamid Iqbal; Khalid, Dr Fahad Khalid (Journal of the Pakistan Medical Association, 2024)
Endomyocardial fibrosis secondary to hyper-eosinophilic syndrome also known as Loeffler’s Endocarditis is a rare cause of restrictive cardiomyopathy. If left untreated, it carries a very high morbidity and mortality rate. The case of a 20 years old girl, a known case of polyarticular juvenile idiopathic arthritis since the age of 13 years was reported at Federal Government Polyclinic Hospital, Islamabad on 14th May 2022. She presented with an acute history of shortness of breath and cough for two weeks. Her initial echocardiogram showed suspicion of Loeffler’s Endocarditis, which is attributed to be an adverse effect of etanercept- a tumour necrosis factor (TNF) inhibitor, which she had been prescribed for her arthritis. The patient is currently being managed with high doses of steroids, therapeutic anticoagulation with rivaroxaban, carvedilol for tachycardia and mycophenolate mofetil as an immunosuppressant. Key Words: Endomyocardial fibrosis, Juvenile Idiopathic Arthritis (JIA), TNF alpha inhibitors, Hyper-eosinophilic syndrome (HES).